2022
DOI: 10.38035/jlph.v2i2.87
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Behavior, Principles and Law Abiding on Business Ethics

Abstract: Literature Review Article Determination of Behavior, Principles and Legal Obedience to Business Ethics is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Business Law. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Effective working relationships between employees, colleagues, and customers. Business activities are affected by responsible conduct, such as preventing plagiarism (Haitao, 2022). Prior research revealed that self-employed cyclists had the highest percentage of helmet use, followed by students and the unemployed (Sharif et al, 2022).…”
Section: Law Abiding Behavior and Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective working relationships between employees, colleagues, and customers. Business activities are affected by responsible conduct, such as preventing plagiarism (Haitao, 2022). Prior research revealed that self-employed cyclists had the highest percentage of helmet use, followed by students and the unemployed (Sharif et al, 2022).…”
Section: Law Abiding Behavior and Occupationmentioning
confidence: 99%
“…Besides that, legal consciousness is a belief in the legal values inherent in humans. Moreover, institutional law such as that found in university, is just as important as the laws enacted by society and the government (Haitao, 2022). Due to the lack of effective rules, new types of rights violations always appear as technology advances.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tyler, law-abiding individuals are motivated to voluntarily obey the law, because they recognize law obedience behavior as both socially appropriate and ethical 14 . Law-abiding behaviors originate from recognition of an existing law (law awareness) and perception of the law as a social value and obeying it as a law 15 . Therefore individuals' obedience to law requires belief in values contained in psychosocial and cultural context 14 .…”
Section: Introductionmentioning
confidence: 99%